The Effect of Game Card-Based Nutrition Education on Knowledge and Attitudes toward Healthy Snacks among Elementary School Students - Sri Hastuti Lestarini (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
School snacks play a significant role in meeting daily energy needs, yet unhealthy snack consumption remains prevalent among elementary school students. Nutrition education is needed to improve students' knowledge and attitudes regarding healthy snack choices. This study aimed to analyze the effect of game card-based nutrition education on elementary school students' knowledge and attitudes about healthy snacks in Ternate City. This study used a quasi-experimental method with a two-group pretest–posttest design. The sample consisted of 51 fifth-grade students, divided into an experimental group (27 students) and a control group (24 students), selected using a purposive sampling technique. Data collection used a knowledge test and attitude questionnaire before and after the intervention. The experimental group received game card-based nutrition education, while the control group received nutrition education using PowerPoint presentations. Data analysis was performed using an independent t-test and a Mann–Whitney test with a significance level of p-value <0.05. The results showed a significant difference in knowledge gain between the experimental and control groups (p-value = 0.001), with a higher increase in knowledge in the experimental group. Furthermore, there was a significant difference in attitude improvement between the two groups after the education (p-value = 0.002). It was concluded that game card-based nutrition education significantly improved elementary school students' knowledge and attitudes about healthy snacks. Game card media can be recommended as an effective and applicable alternative nutrition education medium for school health promotion programs.